2008
DOI: 10.1073/pnas.0710997105
|View full text |Cite
|
Sign up to set email alerts
|

Mating induces an immune response and developmental switch in theDrosophilaoviduct

Abstract: Mating triggers physiological and behavioral changes in females.To understand how females effect these changes, we used microarray, proteomic, and comparative analyses to characterize gene expression in oviducts of mated and unmated Drosophila females. The transition from non-egg laying to egg laying elicits a distinct molecular profile in the oviduct. Immune-related transcripts and proteins involved in muscle and polarized epithelial function increase, whereas cell growth and differentiation-related genes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
106
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 38 publications
10
106
1
1
Order By: Relevance
“…Additionally, recent reports by Kapelnikov et al (33,34) show that mating up-regulates genes and proteins with known roles in muscle and epithelial differentiation in the oviduct (33), and that structural changes occur in the oviduct postmating (34). Analogous changes may occur in the uterus postmating.…”
Section: Uterine Conformational Changes Are Important For Maximal Spermmentioning
confidence: 99%
“…Additionally, recent reports by Kapelnikov et al (33,34) show that mating up-regulates genes and proteins with known roles in muscle and epithelial differentiation in the oviduct (33), and that structural changes occur in the oviduct postmating (34). Analogous changes may occur in the uterus postmating.…”
Section: Uterine Conformational Changes Are Important For Maximal Spermmentioning
confidence: 99%
“…to the foreign proteins contained in the male's seminal fluid [43][44][45]. Finally, part of the changes in the female reproductive tract is in response to manipulative proteins from the male transcriptome in the form of accessory gland proteins (ACPs) [41,46,47], which stimulate female oogenesis and ovulation, as well as impede female remating [47].…”
Section: Short-term Gene Expression Dynamics In Response To Courtshipmentioning
confidence: 99%
“…Part of this is due to the female's innate transcriptomic preparations for embryo provisioning [43]. In addition to this, the female reproductive system stages an immune response [15]; also prevalent in mammalian transcriptomes [16] can occur when splicing is regulated by sex determination pathway or by sexhormone receptors imprinting either the paternal or maternal allele is expressed in the offspring involved in sex determination pathway in some insects [17], some medical conditions [18]; may be common in mammals [19,20] but this remains contentious [21] presumably, methylation patterns in the parental gametes are maintained in the zygote; alternatively, imprinting requires some sort of sensing mechanism to identify parent of origin rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120047…”
Section: Short-term Gene Expression Dynamics In Response To Courtshipmentioning
confidence: 99%
“…However, while different female genotypes associate with differences in sperm competition outcomes, little is known about the specific genes or gene variants that underlie the differences in the female side of sperm competition. Gene expression analyses in singly mated (Lawniczak and Begun 2004;McGraw et al 2004McGraw et al , 2008McGraw et al , 2009Kapelnikov et al 2008) and doubly mated (Innocenti and Morrow 2010) females found numerous genes regulated by mating. These mating-regulated genes may include some that are important for sperm competition.…”
mentioning
confidence: 99%